Synchronous Malignant Peripheral Nerve Sheath Tumor and Adenocarcinoma of the Prostate: Case Report and Literature Review - Nikolaos Ferakis; Antonios Katsimantas; Konstantinos Bouropoulos; Antonios Farmakis (Case Reports in Urology)
Malignant Peripheral Nerve Sheath Tumors (MPNSTs) of the prostate are extremely rare. A very unusual case of simultaneous adenocarcinoma and MPNST of the prostate is reported. A 60-year-old Caucasian male presented for annual urologic examination. Digital rectal examination revealed a painless, toughish, and asymmetrically enlarged prostate. Serum prostate-specific antigen was 1 ng/mL. Radiologic examinations demonstrated a large mass, which was arising from the left peripheral lobe of the prostate. The patient underwent transrectal ultrasound-guided biopsy of the prostate which revealed a smooth muscle tumor of uncertain malignant potential. Radical retropubic prostatectomy with en bloc removal of the mass and the seminal vesicles was performed and histology demonstrated low-grade MPNST and adenocarcinoma of the prostate. To the best of our knowledge, this is the first report of simultaneous prostatic adenocarcinoma and MPNST in the English literature.